SuperCADEs: Introducing One-Stop Government Service Shops in Bogota, Colombia, 2004-2008 - Andrea, Natalia; Vega, Diaz (KDI School of public policy and management, Global Delivery Initiative, 2020)
Before 2004, public agencies and private companies in Bogotá, Colombia were spread out widely across the city. Citizens had to move from one area to another depending on the type of procedure they required, and almost always experienced long travel and waiting times to access services. To solve the problem, in February 2004, the city opened a one-stop-shop—dubbed “SuperCADE”—where citizens could access more than 200 public services from local and national level institutions. To implement the one-stop shop services, the city government had to mend inter-administrative agreements and train staff to improve the quality of attention to the citizens. Despite initially only offering 40 percent of the planned services, citizen demand exceeded expectations. Initial calculations estimated 2,000 people would show up on the first day, however, more than 6,000 citizens passed through the SuperCADE after just half a day. Setting up the first SuperCADE in Bogotá laid the foundations for the government to set up more of these service centers, greatly improving the quality and efficiency of services that citizens received.